Lola Rosa - Wilson, Jacqueline; Sharratt, Nick , illus (London : Corgi Books, 2007)
When life at home suddenly gets really frightening , Jayni, her mum and her little brother Kenny have to pack their bags and escape in the middle of the night. They also have to choose new names and so Jayni becomes the glamorous, grown-up Lola Rose.
Keywords: Adventure and adventurers -- Fiction; Growing up -- Fiction; New life -- Fiction